Biology of invertebrates - Pechenik, Jan A (New York : Mc Graw Hill, 2015)
This textbook is the most concise and readable invertebrates book in terms of detail and pedagogy (other texts do not offer boxed readings, a second color, end of chapter questions, or pronunciation guides). All phyla of invertebrates are covered (comprehensive) with an emphasis on unifying characteristics of each group.
Glossary 587-589p.; Index 590-606p.
Keywords: Annelids; Arthropods; Echinoderms; Nemerteans; Protists